ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETIDAKIKUTSERTAAN PASANGAN USIA SUBUR (PUS) DALAM PROGRAM KELUARGA BERENCANA DI KECAMATAN PUJUD KABUPATEN ROKAN HILIR - Yayuk Kurniawati; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research do in the Pujud subdistrict, Rokan Hilir regency it aimed to find out how form character fertile age couple out of it family planning and factors which influence out of it family planning. The tittle of research is ” Analysis Factors To Influence Out Of It The Fertile Age Couple In Family Planning Program At Pujud Subdistrict, Rokan Hilir Regency”. Main problems in the research is how fertile age couple character out of it fam ily planning program and factors wihich influence. Population in the research is fertile age couple out of it family planning program, have a more two children. Exraction sampling in the research with purposive sampling technic. Total population out of it program family planning program in the 2011-2013 years amount 489 fertile age couple, takeable sampling 48 fertile age couple representatively of population. The method is quantitative descriptive method with quantitative and qualitative analysis data. Insrument extraction data is observation, kuesioner and guided interview as well as tabulation data in the single tabulation data and diagram. General result research of researcher show that fertile age couple out of it family planning program subjection mean of respondent attain the age 40 years old, generally elementary school graduate,have income 2.000.000,00->3.000.000,00 rupiah, moslem, majority is farmer, dominant is Java, have a 4-8 children and the last 44 fertile age couple join family planning program around 3-5 years ago. Dominant factor which influence out of it fertile age couple in research is culture, age, and health.Keywords: Fertile Age Couple, Out of it Family Planning, Family Planning Program.